2020
DOI: 10.1111/1750-3841.15045
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adding solid and molten chocolate on the physicochemical, antioxidant, microbiological, and sensory properties of ewe's milk cheese

Abstract: A novel dairy product, namely “chocolate cheese”, was produced with two typical Sicilian food products: Pecorino cheese, processed from ewe's milk, and Modica chocolate. The cheese, manufactured with 0%, 5%, 10%, and 15% (w/w) solid or molten chocolate, was evaluated after 0, 2, 4, and 6 weeks of vacuum storage for its nutritional and health properties. The addition of chocolate reduced the pH, protein, fat, and ash; the addition of 5% or 10% molten chocolate reduced hardness (N/mm2). The addition of either so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 60 publications
0
6
1
Order By: Relevance
“…The health-promoting index (HPI) [(n-3 PUFA + n-6 PUFA + MUFA)/(C12:0 + (4 × C14:0) + C16:0)] and thrombogenic index (TI) [(C14:0 + C16:0 + C18:0)/((0.5 × Σ MUFA) + (0.5 × Σ n-6 PUFA) + (3 × Σ n-3 PUFA) + (n-3/n-6))] were calculated, respectively, as suggested by Ashkezary et al [ 32 ] and Ulbricth and Southgate [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…The health-promoting index (HPI) [(n-3 PUFA + n-6 PUFA + MUFA)/(C12:0 + (4 × C14:0) + C16:0)] and thrombogenic index (TI) [(C14:0 + C16:0 + C18:0)/((0.5 × Σ MUFA) + (0.5 × Σ n-6 PUFA) + (3 × Σ n-3 PUFA) + (n-3/n-6))] were calculated, respectively, as suggested by Ashkezary et al [ 32 ] and Ulbricth and Southgate [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…in Cuba, but higher than results mentioned byAshkezary et al (2020) in Italy andEspinoza et al (2020) in Ecuador. According to the regulation CE N° 2073/2005, pasteurized milk and other pasteurized liquid dairy products with an Enterobacteriaceae level higher than 10 CFU/mL are considered unsatisfactory, therefore, a control of the heat treatment efficiency, prevention of recontamination and quality control of raw materials should be done.…”
contrasting
confidence: 48%
“…The shear stress versus shear rate data for molten chocolate samples at 40°C was fitted to Casson, Herschel–Bulkley, and Bingham models. Ashkezary, Yeganehzad, Vatankhah, Todaro, and Maghsoudlou (2018) studied different models and concluded that the Casson model was the most appropriate one to represent the rheological behavior of chocolate products. Aydemir, Beşir, and Aden (2021) found that both the correlation coefficients for Casson and Herschel–Bulkley models ( R 2 ) were high.…”
Section: Resultsmentioning
confidence: 99%
“…ples at 40 C was fitted to Casson, Herschel-Bulkley, and Bingham models Ashkezary, Yeganehzad, Vatankhah, Todaro, and Maghsoudlou (2018). studied different models and concluded that the Casson model was the most appropriate one to represent the rheological behavior of chocolate products Aydemir, Bes ¸ir, and Aden (2021).…”
mentioning
confidence: 99%